Complications of Progesterone Therapy for Threatened Abortion in a Cross Bred Cow - KRISHNA, K MOULI; NAIDU, K VENUGOPAL (The Indian Journal of Animal Reproduction, 2023)
Abortions are common in bovines under field conditions. Administration of progesterone to prevent abortions is common under field condition. If the foetus is already dead, progesterone administration may lead to complications. This communication reports the expulsion of a dead foetus with PGF2 in progesterone arrested abortion in a cross bred cow.